2018
DOI: 10.1111/tpj.13830
|View full text |Cite
|
Sign up to set email alerts
|

In the grass species Brachypodium distachyon, the production of mixed‐linkage (1,3;1,4)‐β‐glucan (MLG) occurs in the Golgi apparatus

Abstract: Mixed-linkage (1,3;1,4)-β-glucan (MLG) is a glucose polymer with beneficial effects on human health and high potential for the agricultural industry. MLG is present predominantly in the cell wall of grasses and is synthesized by cellulose synthase-like F or H families of proteins, with CSLF6 being the best-characterized MLG synthase. Although the function of this enzyme in MLG production has been established, the site of MLG synthesis in the cell is debated. It has been proposed that MLG is synthesized at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…In the cellulose synthase-like gene family, CSLF genes are only found in grasses and CSLF6 is the most highly expressed member of this gene family (Burton et al, 2008;Christensen et al, 2010;Kaur et al, 2017). The location of CSLF6 and MLG synthesis is controversial, as one study in barley (Hordeum vulgare) found that MLG is synthesized at the plasma membrane (Wilson et al, 2015), while another study using tobacco (Nicotiana tabacum) epidermal cells expressing B. distachyon CSLF6 and B. distachyon plants overexpressing CSLF6 demonstrated that MLG is synthesized in the Golgi apparatus (Kim et al, 2015(Kim et al, , 2018, supporting the conclusion of Carpita and McCann (2010), who had shown by in vivo radiolabeling that MLG is synthesized in the Golgi apparatus in maize (Zea mays).…”
mentioning
confidence: 99%
“…In the cellulose synthase-like gene family, CSLF genes are only found in grasses and CSLF6 is the most highly expressed member of this gene family (Burton et al, 2008;Christensen et al, 2010;Kaur et al, 2017). The location of CSLF6 and MLG synthesis is controversial, as one study in barley (Hordeum vulgare) found that MLG is synthesized at the plasma membrane (Wilson et al, 2015), while another study using tobacco (Nicotiana tabacum) epidermal cells expressing B. distachyon CSLF6 and B. distachyon plants overexpressing CSLF6 demonstrated that MLG is synthesized in the Golgi apparatus (Kim et al, 2015(Kim et al, , 2018, supporting the conclusion of Carpita and McCann (2010), who had shown by in vivo radiolabeling that MLG is synthesized in the Golgi apparatus in maize (Zea mays).…”
mentioning
confidence: 99%
“…By far the best characterized enzyme in MLG synthesis is CslF6, which has been studied in barley, wheat (Triticum aestivum), rice, maize and B. distachyon (Nemeth et al, 2010;Vega-Sanchez et al, 2012;Kim et al, 2015Kim et al, , 2018. BdCslF6 protein is localized to the Golgi membrane, with an external catalytic domain (Kim et al, 2015(Kim et al, , 2018. Antibody detection of (1,3;1,4)-b-glucan in maize also supports a Golgi-localized synthesis of MLG (Carpita & McCann, 2010).…”
Section: Mixed-linkage Glucansmentioning
confidence: 88%
“…Members of CslF/H/J clades have been shown to be capable of synthesizing (1,3;1,4)-b-glucan when heterologously expressed, but it is not clear whether all of these groups are responsible for native MLG synthesis. By far the best characterized enzyme in MLG synthesis is CslF6, which has been studied in barley, wheat (Triticum aestivum), rice, maize and B. distachyon (Nemeth et al, 2010;Vega-Sanchez et al, 2012;Kim et al, 2015Kim et al, , 2018. BdCslF6 protein is localized to the Golgi membrane, with an external catalytic domain (Kim et al, 2015(Kim et al, , 2018.…”
Section: Mixed-linkage Glucansmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Furthermore, amounts of pectic polysaccharides are lower in the type II cell wall than in the type I cell wall 20 and mixed-linkage β-glucan abundant in the grass cell wall is produced in the Golgi. 21 These indicate that the Golgi organization in maize cells involved in cell wall polysaccharide synthesis differs significantly from that in Arabidopsis and alfalfa cells. However, remodeling of the Golgi stack associated with the synthesis and secretion of XGA in the border/border-like cells of the three plant species seems to be conserved.…”
mentioning
confidence: 94%